The Gatekeepers (Global Journal of Human-Social Science, 2022)
The Gatekeepers" describes the reaction of a handful of well established Israel Studies scholars to a special issue of the journal Israel Studies called "Word Crimes: Reclaining the Language of the Israeli-Palestinian Conflict". These professors preferred to denounce rather than engage with the arguments and analyses presented in the special issue deploying their authority to try to silence this challenge to the conventional discourse on the Middle East Conflict.
Keywords: word crimes; israeli-palestinian conflict; academic discourse; settler colonialism; imperialism; Zionism